Android-Based Educational Learning Game For Children Based On Android - Nunuk Wahyuningtyas; Edo Yonatan Koentjoro (Universitas Muhammadiyah Sidoarjo, 2020)
The purpose of this study is as a means of learning English with the game method is one of the innovations that are suitable and much favored by children. Because children still have a tendency to play. So using this game media is a solution to make it easier for children to learn to recognize English. This research uses the development method used in this Jhony Adventure educational game which is the ADDIE method (Analysis, Design, Developer, Implementation, and Evaluation). The aspect value obtained from functionality testing reaches 100% very good, reliability testing reaches 100% very good, compability testing reaches 100% very good category, and playability testing reaches 96% with very good category. So that the feasibility of the educational game Jhony Adventure is categorized as very feasible. Based on the results of the questionnaire obtained, the educational game Jhony Adventure became an effective alternative solution in the learning of PAUD and Elementary School students in grades 1-2. By using the concept of education as a medium in learning subjects that seem difficult to learn, namely English lessons. Game development is very suitable and effective to help students learn English.